The First Principle in Late Neoplatonism : A Study of the One's Causality in Proclus and Damascius - Greig, Jonathan (Philosophia Antiqua, 2020)
In The First Principle , Jonathan Greig examines the philosophical theology of the two Neoplatonists, Proclus and Damascius (5th-6th centuries A.D.), on the One as the first cause. Both philosophers address a tension in the Neoplatonic tradition: namely that the One was seen as absolutely transcendent, yet it was also seen as intimately related to other things as the source of their unity and being. Proclus' solution is to posit intermediate causes after the One, while Damascius posits a distinct principle, the 'Ineffable', above the One. This book provides a new, thorough study of the theories of causation that lead each to their respective position and reveals crucial insights involved in a rigorous negative theology employed in metaphysics.